Positive Solutions for Certain Classes of Fourth-Order Ordinary Elliptic Systems - Ubilla-Lopez, P (Springer US, 2017)
Using fixed-point techniques, we study the existence of positive solutions for a class of fourth-order ordinary elliptic systems. To this end, we reduce our problem to an appropriate functional differential equation. © 2015, Springer International Publishing Switzerland.